Respostas

A melhor resposta!
2014-05-17T13:47:44-03:00
Relaçao fundamental da trigonometria:

sen²x+cos²x=1

vamos  desenvolve-la
primeiro no sec²x+cossec^2x



=sec^2x+cossec^2x \\  \\=  (\frac{1}{cosx}) ^2+( \frac{1}{senx} )^2 \\  \\ = \frac{1}{cos^2x}+ \frac{1}{sen^2x} \\  \\ = \frac{sen^2x+cos^2x}{cos^2x.sen^2x}    \\  \\ = \frac{1}{cos^2x.sen^2x}



agora o sec²x.cossec²x



=sec^2x.cossec^2x \\  \\ = \frac{1}{cos^2x}. \frac{1}{sen^2x}   \\  \\ = \frac{1}{cos^2x.sen^2x}

Como pode ver da a  mesma coisa
2 5 2